Preparation of NaA zeolite with graphite tailings and its adsorption of ammonia nitrogen - Jun Zhang; Zhen Jia; Sheng Qian; Zhaoyang Li; Zihao Wang; Yuxin Ma (Scientific Reports)
Abstract Environmental pollution caused by the accumulation of graphite tailings (GT) is a significant global challenge. In this study, GT was utilized as a raw material to synthesize NaA zeolite (GTA), with synthesis conditions optimized. The synthesized GTA was characterized by SEM, EDS, BET, XRD, and FTIR, and its ammonia nitrogen (AN) adsorption performance was investigated under varying conditions, including dosage, pH, adsorption time, and temperature. The optimized synthesis conditions were an alkali melting temperature of 700 °C, alkali-ore ratio of 1.2:1, aging time of 8 h, hydrothermal temperature of 90 °C, liquid–solid ratio of 6:1, and hydrothermal time of 8 h, yielding a specific surface area of 36.62 m2/g. In a 100 mg/L AN solution at pH 7 and 30 °C, GTA exhibited an adsorption capacity of 13.88 mg/g within 1 h. The adsorption process follows a pseudo-second-order kinetic model. The adsorption isotherm conforms to the Langmuir model, suggesting that the mechanism involves uniform monolayer adsorption on the surface. The adsorption of AN on zeolite is primarily controlled by chemical rather than physical adsorption. This study provides a foundation for the resource utilization of GT and AN treatment, with practical environmental implications.